PENGARUH KINERJA KEUANGAN DAN CORPORATE SOCIAL RESPONSIBILITY TERHADAP NILAI PERUSAHAAN (STUDI EMPIRIS PERUSAHAAN PERBANKAN YANG TERDAFTAR DI BURSA EFEK INDONESIA TAHUN 2012-2014 - Nelli Novyarni (Jurnal Ekonomi, 2016)
Abstract- Factors known value of the company as follows. Factor financial performance and Corporate Social Responsibility one that affects the value of the company. This study aimed to test whether the effect of Financial Performance and Corporate Social Responsibility (CSR) to Corporate Value on banking company listed on the Indonesia Stock Exchange (BEI). This research uses descriptive quantitative approach, which is measured using multiple linear regression based SPSS 21.0. the population of this study is the banking companies listed in Indonesia Stock Exchange (BEI) in 2012 through 2014. The sample was determined by purposive sampling method, with a sample of 17 banking companies, bringing the total observation in this study were 51 observations. The data used in this research is secondary data. The data collection technique using the method of documentation via the official website IDX: www.idx.co.id. Hypothesis testing using t test. The research proves that (1) Financial Performance affect the Company's value in the banking companies listed on the Stock Exchange 2012-2014, (2) Corporate Social Responsibility positive effect is not significant to the Company's value in banking companies listed on the Stock Exchange 2012-2014, (3) financial performance and Corporate Social Responsibility collectively together have an influence on the value of companies in bannking companies listed on the stock exchange 2012-2014.